Retrospective study on efficacy and safety of nanoparticle paclitaxel and concurrent radiotherapy in patients with advanced head and neck cancer - Chandrakar, Pradeep K.; Rathore, Vikram B.; Choudhary, Vivek (International Journal of Research in Medical Sciences, 2017)
Background: Advanced (Stage III and IV) Squamous Cell Carcinomas of the head and neck (SCCHN) produce severe functional impairment, considerable morbidity, and significant mortality. Over the past 2 decades, organ-sparing efforts using either induction chemotherapy or concurrent chemotherapy and radiotherapy (RT) have become popular and have demonstrated equivalent or superior survival rates compared with surgery and/or RT alone, with a survival rate of approximately 40% at 5 years. Although the addition of chemotherapy to RT enhances toxicity, randomized trials and meta analyses have documented improved survival clearly compared with the results from RT alone. Initially, most combinations included once-daily RT combined with cisplatin either alone or with 5-fluorouracil (5-FU). There was number of toxicities of high grades associated with these drugs, and also difficulty in their administration. We have retrospectively studied nanoparticle paclitaxel with RT on concurrent setting as an alternative. Methods: We have retrospectively studied data of patients of advanced SCCHN treated with nanoparticle paclitaxel along with RT. Nanoparticle paclitaxel was administered at a dose of 80 mg/m2 over one hour infusion once weekly along with RT, 60 Gray (Gy) in 30 fractions, five days per week, over 6 weeks. Results: Total numbers of patient in this study were 28 with median age of 49 years. 78.57% of patient had stage IV disease and 21.43% stage III. Overall response rate was 68% with complete response (CR) in 29% and partial response (PR) in 39%. Conclusions: The use of nanoparticle paclitaxel along with RT is safe, feasible, efficacious and cost effective. Intensive randomized studies with large sample size are required in this direction.